Cybersecurity in accounting education: accounting academics' perspectives - Rama, Pranisha; Marx, Ben; Smith, Rozanne (Frontiers in Education, 2025)
IntroductionCyberattacks continue to intensify and are currently the top global technological risk. This global increase in cyberattacks and the growing dependence on digital platforms have also heightened the significance of cybersecurity within the accounting profession. As future custodians of sensitive financial data, accounting students must possess both the technical understanding and the practical skills to prevent such threats. Given the importance of the digital economy within the accounting profession, accounting curricula often do not include cybersecurity education, resulting in accounting students being inadequately prepared. This research aimed to fill this gap by formulating cybersecurity education guidelines through competencies for an accounting curriculum and is designed to be incorporated into various modules throughout the curriculum.MethodsContent analysis was conducted as part of the literature review to determine which competency frameworks of accounting professional bodies were relevant and which cybersecurity competency statements were to be included in the questionnaires as part of the quantitative study. While the study is predominantly quantitative in nature, the incorporation of participant comments adds a minor qualitative dimension, making the overall design descriptive with supportive qualitative elements. The questionnaire was distributed to accounting academics, and 41 responses were received.ResultsThe findings from this study indicate that accounting academics lack knowledge around cybersecurity and do not know how to incorporate the topic into the curriculum. Academics have also viewed cybersecurity as an important component of the accounting curriculum, given its emphasis within the digital economy.DiscussionThis study contributes to the development of the accounting curriculum and highlights the importance in developing cybersecurity skills in future accounting professionals which can be incorporated by making use of real-life case studies, using experts from the cybersecurity industry.